2019
DOI: 10.1002/jccs.201900205
|View full text |Cite
|
Sign up to set email alerts
|

Solvent effects on the geometry, electronic structure, and bonding style of Zn(N5)2: A theoretical study

Abstract: Nitrogen‐rich compounds involving the cyclo‐pentazole anion (cyclo‐N5−) have attracted extensive attention due to higher energy release and environmental friendliness than traditional high energy density materials (HEDMs). However, the synthesis of stable HEDMs with cyclo‐N5− is still a challenge. In this study, the effect of nine solvents on the geometrical and electronic structures and solvation energies of Zn(N5)2, one of the recently synthesized nitrogen‐rich compounds, was studied using the density functi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…69 After simulating with the empirical Kamlet−Jacobs equations, the detonation velocity and detonation pressure of P1-Zn(N 5 ) 2 phase were estimated up to 12 km/s and 75 GPa, which is closely 2 and 4 times as much as that of TNT. Through comparing the detonation behavior of the salt containing cyclo-N 5 ions in AN 5 (A = H, K, Ru) 70−72 and M(N 5 ) 2 (M = Mg, Zn, Ba, Be), 73,74 the advantages of using metal cations doping are helpful to increase energy density and explosive heat.…”
Section: Computational Methods and Detailsmentioning
confidence: 99%
“…69 After simulating with the empirical Kamlet−Jacobs equations, the detonation velocity and detonation pressure of P1-Zn(N 5 ) 2 phase were estimated up to 12 km/s and 75 GPa, which is closely 2 and 4 times as much as that of TNT. Through comparing the detonation behavior of the salt containing cyclo-N 5 ions in AN 5 (A = H, K, Ru) 70−72 and M(N 5 ) 2 (M = Mg, Zn, Ba, Be), 73,74 the advantages of using metal cations doping are helpful to increase energy density and explosive heat.…”
Section: Computational Methods and Detailsmentioning
confidence: 99%
“…Rajeswarapalanichamy et al reported that ZnN with the space group F 4̅3 m is the lowest energy phase at ambient pressure . Zn 3 N 2 is a direct bandgap n-type semiconductor structure, which has been studied recently as a promising material with great potential for photonic and electronic applications. Binary metal azide Zn­(N 3 ) 2 is a preferred precursor for the synthesis of nitridophosphates and binary nitrides. Recently, Ding et al reported a new Zn­(N 5 ) 2 in the solution phase involving the cyclo-pentazole anion with a stabilization mechanism considered by the charge transfer and the hydrogen bonds between Zn­(N 5 ) 2 and water . Until now, the investigations of zinc nitride compounds were limited to these four stoichiometries; no other Zn–N chemical stoichiometries were reported.…”
mentioning
confidence: 99%
“…30−32 Recently, Ding et al reported a new Zn(N 5 ) 2 in the solution phase involving the cyclo-pentazole anion with a stabilization mechanism considered by the charge transfer and the hydrogen bonds between Zn(N 5 ) 2 and water. 33 Until now, the investigations of zinc nitride compounds were limited to these four stoichiometries; no other Zn−N chemical stoichiometries were reported. The high pressure phase diagrams of zinc nitride compounds as well as their novel physical or chemical properties are still unclear.…”
mentioning
confidence: 99%
“…Cyclo -N 5 – has been predicted to be stabilized by coordinating with various metallic elements (Li, ,, Na, K, Rb, Cs, Be, Mg, , Ca, Sr, Ba, Al, , Ga 7 , Sc 7 , Y 7 , Cu, Zn), among which LiN 5 possesses the highest cyclo -N 5 – content (weight ratio ∼91%). Seven crystal structures ( P 2 1 -LiN 5 , P 2 1 / m -LiN 5 , P 2 1 / c -LiN 5 , C 2/ c -LiN 5 , P 6 1 22-LiN 5 , P 2 1 2 1 2 1 -LiN 5 , Pnan -LiN 5 ) have been discovered theoretically with different mass densities and energy densities under different pressure conditions, ,, but only one predicted structure ( P 2 1 / m -LiN 5 ) has been synthesized .…”
Section: Introductionmentioning
confidence: 99%